Galectin-3 and Galectin-9 May Differently Regulate the Expressions of Microglial M1/M2 Markers and T Helper 1/Th2 Cytokines in the Brains of Genetically Susceptible C57BL/6 and Resistant BALB/c Mice Following Peroral Infection With Toxoplasma gondii - Liu, Jinfeng; Huang, Shiguang; Lu, Fangli (Frontiers in Immunology, 2018)
Toxoplasmic encephalitis (TE), an opportunistic infection, is a severe health problem in immunocompromised patients. Previous studies have revealed that C57BL/6 mice are susceptible and BALB/c mice are resistant to TE. To investigate the mechanisms involved in the immunopathogenesis of TE in susceptible C57BL/6 and resistant BALB/c mice, both strains of mice were perorally infected with the Prugniuad (Pru) strain of Toxoplasma gondii. Our results showed that compared to BALB/c mice, C57BL/6 mice infected with T. gondii Pru strain had more severe brain histopathological damage, and higher mRNA expression levels of tachyzoite-specific surface antigen 1 (SAG1), bradyzoite-specific antigen 1 (BAG1), interferon gamma (IFNγ), interleukin (IL)-10, arginase1 (Arg1) (M2 marker), galectin (Gal)-3, Gal-9, T. gondii microneme protein 1 (TgMIC1), TgMIC4, and TgMIC6 during the course of infection by using quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR). Further analysis displayed that BALB/c mice showed higher numbers of microglial cells, and higher levels of IL-1β, inducible nitric oxide synthase (iNOS) (M1 marker), and chitinase-3-like protein 3 (Ym1) (M2 marker) in the early infective stage (at days 14 or 35 post infection [p.i.]) compared to C57BL/6 mice; whereas C57BL/6 mice showed higher numbers of microglial cells, and higher levels of IL-10, iNOS (M1 marker), and Ym1 (M2 marker) at days 35, 50, or 70 p.i. compared to BALB/c mice. Correlation analysis showed that significant positive correlations existed between Gal-3 and IL-4/IL-10/iNOS/Ym1, and between Gal-9 and IL-4/Ym1 in C57BL/6 mice; between Gal-3 and IFNγ/Arg1, and between Gal-9 and IFNγ/Arg1 in BALB/c mice. Together, our data demonstrated that different Gal-3 and Gal-9 expressions as well as different positive correlations were found between Gal-3 and Th1/Th2/M1/M2 cytokines or between Gal-9 and Th1/Th2/M2 cytokines in the brains of T. gondii Pru strain-infected C57BL/6 and BALB/c mice.